Occurrence and habitat of softshell turtles (Testudines: Trionychidae) in Sidorejo Village, Lendah Subdistrict, Kulon Progo Regency, Special Region of Yogyakarta Province - Yudha, Donan S.; Muslim, Sheliana N. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2026)
Softshell turtles are freshwater turtles with soft carapaces. Their habitat includes freshwater bodies such as rivers and swamps in tropical and subtropical regions. Data on softshell turtle species and their potential habitats in the freshwater ecosystems of the Special Region of Yogyakarta have not been well documented. Based on information from local residents, a softshell turtle population occurs in Sidorejo Village, Lendah, Kulon Progo, Special Region of Yogyakarta. Accordingly, this study aimed to examine the species and potential habitat of softshell turtles in Sidorejo Village, Lendah, Kulon Progo, Special Region of Yogyakarta. Sampling was conducted from 2 February to 17 April 2020 in Kedung Ingas Stream, Sidorejo Stream, and Andong Stream using the Purposive Sampling method. The results showed that the softshell turtle species found was Amyda cartilaginea. The habitat was characterized by shallow streams with depths of 20–70 cm and widths of 150–250 cm, muddy substrates with leaf litter, clear water available throughout the year, calm currents, and riparian vegetation with canopy cover such as water apple, guava, gayam, thorny bamboo, apus bamboo, and lempeni. Softshell turtle nests were characterized by their location under trees, fragments of crab shell in front of the nest cavity, small bubbles in front of the cavity, nest forms resembling cavities in soil or solid rock, and isolated nest sites. These three streams are potential habitats for softshell turtles.